Development of Digital Peer Based Pocket Book on Social Behavior of Cerebral Palsy Disability - Anggraini Oktafiolita; Endang Pudjiastuti Sartinah; Murtadlo Murtadlo (STKIP Taman Siswa Bima, 2025)
This study aims to develop a digital pocket book that can help improve social behavior in individuals with cerebral palsy (CP) through a peer-based approach. Cerebral palsy often affects motor and communication skills, limiting social interactions with peers. Therefore, technology can provide a solution to enhance their social skills. This digital pocket book is designed with features that facilitate communication and social interaction through various educational activities tailored to the needs of children with CP. By incorporating inclusive and user-friendly design principles, the application provides easy-to-understand and engaging materials, supporting the development of social behavior in a more interactive environment. The development of this product involves testing with the target group to evaluate its effectiveness and user response. The research findings are expected to contribute to creating more inclusive technology-based solutions that support improved quality of life for children with cerebral palsy, particularly in terms of communication and social interaction with peers.